Anticoagulant prescribing in atrial fibrillation and risk of incident dementia: A UK population‐based cohort study: Developing topics. (7th December 2020) - Cadogan, Sharon L; Powell, Emma; Wong, Angel Y; Wing, Kevin; Smeeth, Liam; Warren‐Gash, Charlotte
Abstract: Background: Dementia risk is approximately doubled among patients with atrial fibrillation (AF) 1‐3, who are often recommended to take blood‐thinning drugs (anticoagulants) to prevent stroke. Recent evidence has also shown that taking anticoagulant drugs may help to delay the onset of dementia among individuals with AF 4, however, we do not know which types of anticoagulants drugs are most beneficial and for which groups of patients. Hence, the aim of this study was to compare the effect of direct oral anticoagulants (DOACs) versus vitamin K antagonists (VKAs) on risks of incident dementia and mild cognitive impairment (MCI) among patients with newly diagnosed atrial fibrillation (AF). Method: Using linked electronic health records data from the Clinical Practice Research Datalink (CPRD) in the United Kingdom, we conducted a historical cohort study among first‐time oral anticoagulant users with patients with incident non‐valvular AF diagnosed from 2012 to 2018. Crude incidence rates of dementia and MCI were calculated overall and separately for DOACs and VKAs. Cox proportional hazards regression models were then used to compare the incidence of clinically coded dementia and MCI between patients prescribed VKAs and DOACs, adjusting for sociodemographic and lifestyle factors, clinical comorbidities and medications. Result: Of 39, 200 first time oral anticoagulant users (44.6% female, median age 76 years, IQR 68‐83), 20, 687 (53%) were prescribed a VKA and 18, 513 (47%) a DOAC at baseline. Overall, 1, 258 patients (3.2%) had GP‐recorded incident dementia, incidence rate 14.9 per 1, 000 person‐years and 1, 483 patients (3.9%) received a diagnosis of MCI, incidence rate 19.29 per 1, 000‐person years. DOAC treatment for AF was associated with a 15% reduction in dementia risk compared to VKA treatment in the whole cohort (HR 0.85, 95% CI: 0.73, 0.98) and with a 20% reduction in MCI risk (HR 0.80, 95% CI: 0.71‐0.91). Conclusion: The risks of incident EHR‐recorded dementia and MCI were lower among patients prescribed DOACs for new AF compared to those prescribed VKAs. The cognitive risk profile of a patient should help to inform choice of oral anticoagulant treatment for AF among older individuals.